Moorish Culture in Don Quixote - BAHOUS, Abbès (Journal of Human Sciences, 2007)
Don Quixote the founding novel written by Cervantes is based on an Arabic text found in the streets ofToledo, the mythical town of translation. Thus, told by Side Hamet Benengeli the Moorish historian, Don Quixote takes an Arabic look. In this claim pure forgery or partly tenable ?